Heartbeat - Wood, Sam, 1883-1949; Rogers, Ginger, 1911-1995; New World Productions Inc.; Cinetel Films ([Los Angeles, CA] : New World Productions Inc., 1946)
A young female (Ginger Rogers) escapee from a reform school joins a pickpocket academy in Paris. She is caught red-handed on her first attempt at stealing by an upper class man. He recruits her to do him a favor at a society party where she meets and falls in love with a young, handsome, rich diplomat. --
Ginger Rogers, Jean Pierre Aumont, Adolphe Menjou, Melville Cooper, Mikhail Rasumny, Eduardo Cianelli, Mona Maris, Henry Stephenson, Basil Rathbone.
Director of photography, Joseph Valentine; editor, Roland Gross, J.R. Whittredge; music, Paul Misraki.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Pickpockets -- France -- Paris -- Drama; Female offenders -- France -- Paris -- Drama; Balls (Parties) -- France -- Paris -- Drama; Romantic comedy films; Feature films; Internet videos; Streaming video